2016
DOI: 10.1038/srep30187
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged secretion of cortisol as a possible mechanism underlying stress and depressive behaviour

Abstract: Stress is associated with the onset of depressive episodes, and cortisol hypersecretion is considered a biological risk factor of depression. However, the possible mechanisms underlying stress, cortisol and depressive behaviours are inconsistent in the literature. This study examined the interrelationships among stress, cortisol and observed depressive behaviours in female rhesus macaques for the first time and explored the possible mechanism underlying stress and depressive behaviour. Female monkeys were vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 49 publications
4
52
0
Order By: Relevance
“…Increased CRH receptor levels in some brain regions (eg, the amygdala and hippocampus) may contribute to pain and depressive mood in the absence of tissue pathology or disease state . However, the results of the relationship between cortisol and depression are inconsistent with findings in the literature …”
Section: Discussionmentioning
confidence: 92%
“…Increased CRH receptor levels in some brain regions (eg, the amygdala and hippocampus) may contribute to pain and depressive mood in the absence of tissue pathology or disease state . However, the results of the relationship between cortisol and depression are inconsistent with findings in the literature …”
Section: Discussionmentioning
confidence: 92%
“…5 This conclusion is supported by other studies in the literature that have shown depression to be linked with increased cortisol levels, in both humans and nonhuman primates. 13,19 Additionally, in a prospective study of 243 patients undergoing elective CABG surgery, Mu et al 11 found high cortisol levels to be linked with postoperative delirium. These elevated glucocorticoid levels have been hypothesized to cause structural changes in hippocampal neurons and to perturb the hypothalamic-pituitary axis, which may predispose the brain to episodes of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the data showing that multiple antidepressants have similar effects on stress hormones in humans and rodents increases confidence that there is sufficient evolutionary conservation between species to carefully model HPA axis dysregulation in rodents to further probe MDD neurobiology. While rodent models have proved extremely valuable in gaining mechanistic insights into the pathophysiology, emerging studies using the non-human primates have begun to offer additional dimensions to the endocrine and behavioral correlates of chronic stress induced MDD (213,214). Exploring the effects of HPA axis modulation in these animal models could provide a bridge to improve our mechanistic understanding of how changes in cortisol cascade to abnormalities in metabolism, gene regulation, and immune function, all of which have been independently implicated in MDD.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%